"Per la conservació de la raça catalana": The Catalan Eugenics Society (1935–1937). Issue 1 (2nd January 2019) - Cleminson, Richard
ABSTRACT: This article expands on existing work done on the Catalan Eugenics Society and its focus on Josep Vandellós, a demographer and organiser of the Society. It places the Catalan Eugenics Society within the growing volume of work on the international, particularly "Latin" eugenics movement. In doing so, it explores discourse on questions of "race, " immigration and "national" identity as refracted through the nascent eugenics movement and the political concerns of the time in Catalonia. In particular, the article assesses the question of "racial mixing" between Catalans and Spaniards from other regions and argues that, rather than rejecting miscegenation outright, Vandellós valued certain mixes as part of a eugenic project to fortify and maintain the Catalan "race" in the face of population loss and the dissolution of Catalan identity.